PELATIHAN SMART PARENTING “KOMUNIKASI PERSUASIF SUGESTIF DAN EFEKTIF TERHADAP ANAK USIA DINI (AUD) PADA KONDISI PANDEMI COVID-19 BAGI ORANG TUA DAN WALI SISWA PAUDIT AL FIKR SURAKARTA - Dewi Agustini (Jurnal Al Basirah, 2021)
Persuasive, suggestive and effective communication is the art of interacting using ways of giving suggestions so that children of AUD age or so-called during the covid-19 pandemic in the stimulation process increase their intelligence. With the suggestions given, it is hoped that they will realize and be enlightened that there is extraordinary potential that they have never optimized in the stimulation process. This AUD stimulation method during the covid-19 pandemic uses techniques that apply in hypnosis. Is a combination of the concept of stimulation activities using the understanding of hypnosis. In practice, parents act as hypnotists while children act as suyet (people who are hypnotized). Parents in practice simply use persuasive language as a communication tool that can effectively suggest children during the COVID-19 pandemic. Use the language of communication in accordance with the expectations of the child. Early Childhood Education (PAUD) is the golden age which holds the foundation for the growth and development of physical and spiritual education. In the process of stimulation or learning during the Covid-19 pandemic, special treatment and appropriate techniques are needed so that the stimulation process is successful. Suggestive and effective persuasive communication is one of the right approaches given to early childhood during the covid-19 pandemic. Because the benefits will provide psychological relaxation. Stimulation during the covid-19 pandemic will feel more fun, peaceful, calm, relaxed, and rich in suggestive meaning.